(untitled) (Global Journal of Science Frontier Research, 2019)
The synthesis of novel non-linear polycyclic diazaphenothiazine and its amido derivatives via Buchwald – Hartwig reaction protocol is reported. By reacting 2-amino-5- bromopyrazine-3[4H ]-thione and 2, 3-dichloro-1, 4- naphthoquinone in the presence of anhydrous sodium carbonate, 9-bromo-6-chloro-8, 11-daiza-5H-benzo[a] phenothiazin-5-one was obtained. The arylation of 9-bromo- 6-chloro-8, 11-daiza-5H-benzo[a]pheno-thiazin-5-one with some amides under palladium catalysis gave the amido derivatives in good yield. The stability of these cyclic quinoneimine systems, which has been attributed to ionic resonance effect, is noted. Structural assignments were based on UV, IR and NMR spectra as well as elemental analysis. These compounds showed significant antimicrobial activity against E. coli, Staphylococcus spp, Bacillus spp. and Pseudomonas aeruginosa at varying concentrations.